Keynes, post-Keynesianism and political economy - Harcourt, G. C. (Geoffrey Colin), 1931-; Kriesler, Peter (Essays in honour of Geoff Harcourt ;, 1999)
Collected here are wide-ranging contributions to economics in general, and to post-Keynesian economics in particular by leading economists.